INTERDISCIPLINARY STUDIESIN EDUCATION - Sysoieva, Svitlana (Continuing Professional Education: Theory and Practice, 2019)
The article shows that the widening of the subject field of modern pedagogy requires research that goes beyond the boundaries of discipline and acquires the features of inter- and multidisciplinarity; a new qualitative level of research in education can be provided on the principles of educology as a scientific direction of an integrated study of the field of education that focuses on objects and phenomena with a «rigid» and broad type of interdisciplinarity that goes beyond the established subject of pedagogy; the criterion for distinguishing pedagogical researches and studies in the field of educology (education sciences) is defined – «the type of interdisciplinary study».